Carne de frango e de galinhas de postura para elaboração de charque - Silva, Fábio Anderson Pereira da (2016)
The aim of this work was to evaluate the effect of processing, storage, desalting and cooking methods on the quality parameters and oxidative stability of lipids and proteins of charqui from broiler and laying hen meat. Initially, we evaluate the effects of processing phases (salting, drying and pressing) and storage on the quality parameters and oxidative deterioration in broiler and laying hen charqui. The processing phase and the time of storage had an effect (p<0.05) on physicochemical and sensory parameters of charqui samples. A marked increase in hardness was identified after processing of analyzes samples, which also presented low rancid scores and a flavor very similar to that of the traditional beef charqui. Storage time influenced the evolution of lipid and protein oxidation, especially in samples processed from hen meat. Muscle type also presented a remarkable impact on the oxidative stability of chicken charqui samples during storage. On the second study, we evaluated the influence of desalting and different cooking methods on the quality attributes and oxidative evolution of lipids and proteins of charqui from broiler meat. Desalting promoted an increase of moisture with a consequent decline in NaCl content of salted and dried samples. High temperatures of cooking affected protein carbonylation, tryptophan fluorescence and disulphide bond formation, while the length of cooking played a major role in free thiol depletion, Schiff Bases formation and instrumental softening of broiler charqui. Samples submitted to desalting and sous-vide cooking showed the highest levels of TBARs, which reflected on their aromatic profile. In fact, most of volatile compounds in desalted and sous-vide cooked samples was derived from lipid oxidation reactions. Heat treatments that applied high temperatures (grilling, roasting and frying) had a significant effect (p<0.05) on meat aroma by the formation of volatile compounds derived from Maillard reaction. Sous-vide cooking promoted low water loss, intense decrease of NaCl content and the improvement of meat texture, and seems to be an advantageous cooking method to prepare broiler charqui. However, sensory aroma of sous-vide cooked samples presented the lowest scores by consumers compared to the other cooking techniques. Furthermore, it was observed that the aroma acceptability in broiler charqui depends on its balanced volatile profile among those derived from lipid oxidation and Maillard reaction. In conclusion, the elaboration of charqui from broiler and laying hen meat seems to be feasible. Desalting and cooking method shows an effect on oxidative stability, quality traits and aromatic profile of salted and dried broiler and laying hen meat.